Utilização do processo sol-gel na obtenção de luminóforos à base de nióbio e íons TR³+ (TR³+=Y³+, La³+, Gd³+ e Eu³+) - Massarotto, Wagner Luis (2017)
White light emitters in the solid state are considered the next-generation light sources, due to its advantages such as long life, low power consumption and environmental issues. However, the luminophore commercially used as a emitter in the red region, yttrium oxysulfide (Y2O2S: Eu3+), features low efficiency when compared with luminophores blue and green light-emitting, low life time under UV radiation and instability due to the release of sulfide gas. In this context, materials based on niobium oxide present promising properties in this field, due to its stability under ultraviolet radiation, they present relatively low photon energy (~900 cm-1 ), they are transparent in a wide wavelength range (0.35 - 9.0 nm) in addition to high levels of refraction (2.4). In this work, niobium based matrices containing Rare Earth ions (Y3+ , La3+ , Gd3+ and Eu3+) were prepared by the adaptation of the nonhydrolytic Sol-Gel process aiming obtain luminophores emitters in the red region. The results indicated that the samples treated at 550 °C for 4 h containing different concentrations of doping ions presented mixtures of structural phases, being hexagonal and monoclinic to Nb2O5 and orthorhombic to Nb3O7Cl, while the 900 °C treated samples showed monoclinic and orthorhombic phases for the Nb2O5 and orthorhombic or monoclinic for phases lanthanum niobate or gadolinium, respectively. In photoluminescence spectroscopy, the spectra showed similar profiles for all samples treated at 900 °C, regardless of the concentration or ion used (Y3+ , La3+ and Gd3+). However, for the sample containing La3+ ion, noticed a decrease in the intensity of transition 7 F0,1 → 5D1, related to the formation of lanthanum niobate phase. In addition, samples treated at 900 °C showed a decrease of the matrix band’s intensity, thinner emission bands and an increase in lifetime of Eu3+ ion when compared with the same samples treated at 550 °C, indicating an increase of crystallinity. Finally, the luminance results indicate that prepared matrices present great potential for application as luminophores emitters in the red region, due to intense emissions when excited in the UV (260 and 394 nm), blue (465 nm) and green (533 nm).